Thermo-mechanical properties of shape memory polymer nanocomposites reinforced by carbon nanotubes. (January 2019) - Hassanzadeh-Aghdam, Mohammad Kazem; Ansari, Reza; Mahmoodi, Mohammad Javad
Highlight: Overall thermomechanical properties of CNT/SMP nanocomposites are studied using the SUC model. Two fundamental aspects are investigated herein; namely, CNT waviness and the existence of an interphase. Increasing CNT volume fraction leads to (i) an increment in the elastic moduli and (ii) a reduction in the CTEs of the CNT/SMP nanocomposite. Employing the straight CNTs within the SMP matrix improves the longitudinal thermomechanical properties of the nanocomposite, whereas the CNT waviness improves the effective transverse properties. Abstract: This work is aimed at a comprehensive characterization of thermoelastic properties of shape memory polymer (SMP) nanocomposites containing carbon nanotubes (CNTs) via a micromechanical model. Two critical aspects affecting the CNT/polymer nanocomposite overall behavior including, the non-straight shape of CNTs and an interphase region formed due to non-bonded van der Waals interactions between a CNT and the SMP are considered. The influences of volume fraction, diameter, aspect ratio, waviness of the CNTs, size and adhesion exponent of the interphase and temperature on the elastic moduli and coefficients of thermal expansion (CTEs) of the CNT/SMP nanocomposites are investigated. The results indicate that the SMP nanocomposite elastic moduli enhance with (i) increasing both the CNT volume fraction and interphase thickness and (ii) decreasing both the CNT diameter and interphase adhesion exponent. Also, the longitudinal elastic modulus of SMP nanocomposites can be significantly increased by using straight CNTs, whereas the transverse elastic modulus improves by employing wavy CNTs. It is observed that the SMP nanocomposite CTEs decrease with the increase in CNT volume fraction, whereas the CNT diameter effect on the thermal expansion response can be ignored. Generally, the results of the presented model are found to be in very good agreement with experiments. Graphical abstract: Image, graphical abstract